Powerful anti‐inflammatory action of luteolin: Potential increase with IL‐38. (23rd March 2021) - Conti, Pio; Caraffa, Alessandro; Gallenga, Carla E.; Ross, Rhiannon; Kritas, Spyros K.; Frydas, Ilyas; Younes, Alì; Di Emidio, Paolo; Ronconi, Gianpaolo; Pandolfi, Franco
Abstract: Luteolin belongs to the flavone family originally present in some fruits and vegetables, including olives, which decrease intracellular levels of reactive oxygen species (ROS) following the activation of various stimuli. Luteolin inhibits inflammation, a complex process involving immune cells that accumulate at the site of infectious or non‐infectious injury, with alteration of the endothelium leading to recruitment of leukocytes. Cytokines have been widely reported to act as immune system mediators, and IL‐1 family members evolved to assist in host defense against infections. Interleukin (IL)‐1 and Toll‐like receptor (TLR) are involved in the innate immunity in almost all living organisms. After being synthesized, IL‐1 induces numerous inflammatory mediators including itself, other pro‐inflammatory cytokines/chemokines, and arachidonic acid products, which contribute to the pathogenesis of immune diseases. Among the 11 members of the IL‐1 family, there are two new cytokines that suppress inflammation, IL‐37 and IL‐38. IL‐38 binds IL‐36 receptor (IL‐1R6) and inhibits several pro‐inflammatory cytokines, including IL‐6, through c‐Jun N‐terminal kinase (JNK) induction and reducing AP1 and nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NFκB) activity, alleviating inflammatory diseases. Therefore, since luteolin, IL‐37 and IL‐38 are all anti‐inflammatory molecules with different signaling pathways, it is pertinent to recommend the combination of luteolin with these anti‐inflammatory cytokines in inflammation.